Kebakaran Lahan Basah dalam Perspekif Masyarakat - Mona Lestari; Fenny Etrawati; Yustini Ardillah; Adisyah Fitria Rahmadini; Titi Nurhaliza (Graduate School Bogor Agricultural University (SPs IPB), 2022)
Perception in the community greatly affects the occurrence of fire because if the community has the intention to burn land it will produce behavior to burn land. The intention in carrying out an action including burning land does not appear suddenly but must go through stages. Behavior Planned Theory states that behavior can be predicted by attitudes toward behavior, subjective norms, and perceptions of behavior control will change the intentions and behavior of individuals. Methods: The study design used in the study is qualitative with a descriptive approach, which is to review and analyze people's perception of fire events in the Ogan Ilir wetlands of South Sumatra. Study informants consist of expert informants and key informants. The expert informants in this study are the Regional Disaster Management Agency, the Subdistrict Head, and the Village Head. Expert informants are the community in the subdistrict at the study site. Results: The results showed that attitudes towards behavior, subjective norms, and perceptions of control had a positive influence on the intention of the people in Ogan Ilir not to burn land. Conclusion: Planned Behavior Theory explains that intention is a function of three determinants. The three determinant components affect the intentions in individuals in the community, namely the community prefers to open land by poisoning grass and using tractors. The intention resulted in the behavior of people who do not burn land to open land.